Developing a coherent monitoring system for Mediterranean grasslands - Louhaichi, Mounir; Johnson MD; Clark, P.E.; Belgacem, A.O.; Johnson D (CIHEAM, 2012)
Grasslands are one of the world's most widespread vegetation types, covering nearly 20% of the land surface and represent a major source of production of agricultural products. However, grassland vegetation across the Mediterranean region is changing at an unanticipated rate. These changes are the result of climatic and socio-economic changes. Because changes in agro-ecosystems affect the livelihoods and development of rural communities, it is important that planners and policy makers be able to determine grassland condition and trend in relation to climatic and managerial factors at specifik locations.